Agent-Based Approach for E-Learning - Bourekkache, Samir; Kazar, Okba (International Journal of Emerging Technologies in Learning (iJET), 2009)
The current life knows a remarkable development which changes all aspects of our life such as: our working environment, educational system, traveling patterns, sport activitiesâ?¦etc. The busy lifestyle faced by individuals today and the fast pattern of life may lead to their inability to be involved in a process of education. There is also a considerable technological development, especially the development of computing and communication technology. All these factors led to the idea of the need to reduce the time and to benefit from this technology, particularly in the field of education. The way of the classical education is very slow, and the student is obliged to be present at specific times which may be inappropriate for the majority of learners. Moreover, the substantial funds allocated for the success of classical learning process. Thus, it emerged the so-called E-learning via the Internet; the aims of this new mode of learning across the network (web) are to reduce the time of a process of learning â??education- as well as to erase the drawbacks of the classical way of education. Therefore, in E-learning, the learner is not forced to be present at specific times, but he is free to choose the time of learning, which is appropriate with his schedule. Another point that is the adaptation of the content (courses) with the intellectual and social characteristics of the learner and with his background (previous knowledge), which is the main task for each educational system. The technology of Multiagent system is relevant in this area.